Trait Self-Control Memoderasi Pengaruh Fear of Missing Out terhadap Prokrastinasi Akademik - Audita Izza Balqis; Putri Citra Andina (Universitas Muhammadiyah Malang, 2022)
Social media has grown rapidly giving an impact on academic activities. Fear of missing out (FoMO) is a phenomenon that develops due to the use of social media, which is thought to be a contributor to academics. This study aims to determinethe effect of FoMO on academic procrastination by considering the role of the trait of self-control. 116 participants ﬁlledout online questionnaires to measure the Academic Procrastination Scale (APS), Brief Self-control Scale (SCS), and Fear of Missing Out Scales (FoMOS). Data analysis was carried out using the moderating regression method, showing that the trait of self-control signiﬁcantly moderated the effect of FoMO on academic procrastination. This study implies that the self-control trait can be used as a reference in reducing the level of academic procrastination.